The perceptual consequences and neurophysiology of eye blinks - Willett, Shawn M.; Maenner, Sarah K.; Mayo, J. Patrick (Frontiers in Systems Neuroscience, 2023)
A hand passing in front of a camera produces a large and obvious disruption of a video. Yet the closure of the eyelid during a blink, which lasts for hundreds of milliseconds and occurs thousands of times per day, typically goes unnoticed. What are the neural mechanisms that mediate our uninterrupted visual experience despite frequent occlusion of the eyes? Here, we review the existing literature on the neurophysiology, perceptual consequences, and behavioral dynamics of blinks. We begin by detailing the kinematics of the eyelid that define a blink. We next discuss the ways in which blinks alter visual function by occluding the pupil, decreasing visual sensitivity, and moving the eyes. Then, to anchor our understanding, we review the similarities between blinks and other actions that lead to reductions in visual sensitivity, such as saccadic eye movements. The similarity between these two actions has led to suggestions that they share a common neural substrate. We consider the extent of overlap in their neural circuits and go on to explain how recent findings regarding saccade suppression cast doubt on the strong version of the shared mechanism hypothesis. We also evaluate alternative explanations of how blink-related processes modulate neural activity to maintain visual stability: a reverberating corticothalamic loop to maintain information in the face of lid closure; and a suppression of visual transients related to lid closure. Next, we survey the many areas throughout the brain that contribute to the execution of, regulation of, or response to blinks. Regardless of the underlying mechanisms, blinks drastically attenuate our visual abilities, yet these perturbations fail to reach awareness. We conclude by outlining opportunities for future work to better understand how the brain maintains visual perception in the face of eye blinks. Future work will likely benefit from incorporating theories of perceptual stability, neurophysiology, and novel behavior paradigms to address issues central to our understanding of natural visual behavior and for the clinical rehabilitation of active vision.